Pelatihan Dasar Pengoperasian Komputer untuk Meningkatkan Kesiapan Peserta Didik MAS DDI Cambalagi Menuju Dunia Perkuliahan - Agussalim Agussalim; Dania Gaffar; Rosmaladewi Rosmaladewi; Nurul Hawa M; Putri Indahsari; Muh Safril Muh Safril (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2025)
The rapid development of digital technology in the era of globalization requires all students to have digital literacy skills in order to be prepared for entering college. The situation at MAS DDI Cambalagi shows that most students still have limited basic computer skills. Therefore, students from the KEMAL (Field Application Teaching Skills) program at Maros Muslim University (UMMA) organized computer training activities to improve students' digital skills. The activity was carried out in several stages, namely mapping the participants' needs, providing material and practical application of Microsoft Office, and evaluation using questionnaires and group discussions. The evaluation results showed a significant increase in abilities, especially in terms of confidence, technical skills, and motivation in developing digital literacy. Data revealed that 85% of participants became more confident, 80% showed improvement in application operation, and 75% demonstrated a higher commitment to continue learning technology. These findings indicate that the training positively contributed to supporting students' academic readiness to meet the demands of technology-based higher education.